2023
DOI: 10.1097/sla.0000000000005843
|View full text |Cite
|
Sign up to set email alerts
|

The Thresholds of Caprini Score Associated With Increased Risk of Venous Thromboembolism Across Different Specialties

Abstract: Objective: Estimation of the specific thresholds of the Caprini risk score (CRS) that are associated with the increased incidence of venous thromboembolism (VTE) across different specialties, including identifying the highest level of risk. Background: Accurate risk assessment remains an important but often challenging aspect of VTE prophylaxis. One well-established risk assessment model is CRS, which has been validated in thousands of patients from many different medical and surgical specialties. Methods: A s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(7 citation statements)
references
References 88 publications
(127 reference statements)
0
7
0
Order By: Relevance
“…Although the Caprini score is the recommended risk assessment model for surgical patients, it is also widely used in medical ones. There is still a lack of proper validation of the Caprini score in many patient populations and clinical situations, and a recently published paper showed that the thresholds of the Caprini score associated with increased risk of venous thromboembolism may vary across different specialties within a score range of 7-11 [86]. Of note, among 68 studies that enrolled more than 4 million patients, only one was conducted in a mixed gynecological and urological surgical population of 783 patients.…”
Section: Risk Assessment Models For the Assessment Of Venous Thromboe...mentioning
confidence: 99%
“…Although the Caprini score is the recommended risk assessment model for surgical patients, it is also widely used in medical ones. There is still a lack of proper validation of the Caprini score in many patient populations and clinical situations, and a recently published paper showed that the thresholds of the Caprini score associated with increased risk of venous thromboembolism may vary across different specialties within a score range of 7-11 [86]. Of note, among 68 studies that enrolled more than 4 million patients, only one was conducted in a mixed gynecological and urological surgical population of 783 patients.…”
Section: Risk Assessment Models For the Assessment Of Venous Thromboe...mentioning
confidence: 99%
“…[15][16][17] Among all, the Caprini risk score (CRS) is the most validated tool to predict postoperative VTE. [18][19][20] However, it has not yet been validated adequately in minimally invasive VV surgery. 20 Also, there is no evidence on the CRS thresholds that may be associated with the benefits of routine pharmacological prophylaxis in patients with VVs undergoing endovenous treatment.…”
Section: Introductionmentioning
confidence: 99%
“…General abdominal, colorectal, upper gastrointestinal (UGI), and hepatopancreatobiliary (HPB) surgery guidelines have failed to provide patient and procedure-specific guidance on pharmacological thromboprophylaxis, 7,[12][13][14][15][16][17] at least in part due to uncertainty regarding baseline risks that vary with patient and procedure-specific factors. 18 The absence of procedurespecific recommendations contributes to substantial practice variation within and between centers and countries. 12,[19][20][21][22][23][24][25] To provide risk estimates of VTE and major bleeding for general abdominal, colorectal, UGI, and HPB procedures, and thus to fill this knowledge gap, we conducted a series of systematic reviews.…”
mentioning
confidence: 99%
“…General abdominal, colorectal, upper gastrointestinal (UGI), and hepatopancreatobiliary (HPB) surgery guidelines have failed to provide patient and procedure-specific guidance on pharmacological thromboprophylaxis, 7,12–17 at least in part due to uncertainty regarding baseline risks that vary with patient and procedure-specific factors 18 . The absence of procedure-specific recommendations contributes to substantial practice variation within and between centers and countries 12,19–25 .…”
mentioning
confidence: 99%